Measurement of Inclusive W and Z Boson Production Cross Sections in pp Collisions at root s=8 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (Amer Physical Soc, 2014)
A measurement of total and fiducial inclusive W and Z boson production cross sections in pp collisions at root s = 8 TeV is presented. Electron and muon final states are analyzed in a data sample collected with the CMS detector corresponding to an integrated luminosity of 18.2 +/- 0.5 pb(-1). The measured total inclusive cross sections times branching fractions are sigma(pp -> WX) x B(W -> l upsilon) = 12.21 +/- 0.03(stat) +/- 0.24(syst) +/- 0.32(lum) nb and sigma(pp -> ZX) x B(Z -> l(+)l(-)) = 1.15 +/- 0.01(stat) +/- 0.02(syst) +/- 0.03(lum) nb for the dilepton mass in the range of 60-120 GeV. The measured values agree with next-to-next-to-leading-order QCD cross section calculations. Ratios of cross sections are reported with a precision of 2%. This is the first measurement of inclusive W and Z boson production in proton-proton collisions at root s = 8 TeV.